Knowledge Of Child Abuse Among Parents Of Under 5 Years Children In Kathmandu, Nepal - Gurung, Lekha Bahadur; Bahattarai, Suraj (Journal of Manmohan Memorial Institute of Health Sciences, 2015)
Child abuse and neglect is a significant global problem with a serious impact on the victims’ physical and mental health, well-being and development throughout their lives. Out of the many parental causes of child abuse, the important reason is lack of knowledge regarding it among them. We explored the knowledge of child abuse among the parent of under 5 children in urban setting of Kathmandu district of Nepal. This is descriptive cross sectional study which involved the parents of children under 5 years of age residing in Kalanki area of Kathmandu in order to identify their existing knowledge on child abuse and to explore the relationships between their knowledge scores and some selected variables by interviewing using a semi-structured questionnaire. Out of the total 95 participants, 50.53% had good knowledge and 48.4% had average knowledge on overall child abuse. None of the parents had poor knowledge in terms of child physical abuse, child neglect and child emotional abuse. However, 20% and 10.5% of the parents had poor knowledge on child sexual abuse and general child abuse respectively. The level of knowledge and the variables viz. age group and exposure to different source of information were significantly associated while no significant association was found with their educational status. The parents do have a satisfactory level of knowledge regarding child abuse. However, a significant proportion of parents still had poor knowledge in context of general child abuse and child sexual abuse. A nationwide study of such kind using qualitative tools as well as conducting awareness raising activities especially focusing on the general abuse and abuse of sexual nature is recommended. DOI: http://dx.doi.org/10.3126/jmmihs.v1i4.11995 Journal of Manmohan Memorial Institute of Health Sciences Vol. 1, Issue 4, 2015 Page : 9-13